Renewable Natural Gas Adoption in Indonesia: A Systematic Literature Review on Green Trust, Perceived Value, and Digital Engagement - Charly Simanullang; Sri Indarti; Alvi Furwanti Alwie; Lailan Tawila Berampu (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Achieving Indonesia’s net-zero emissions target by 2060 requires a green energy marketing strategy that focuses not only on products but also on building trust, social value, and digital participation. This study aims to identify key factors influencing the adoption of renewable natural gas in Indonesia and formulate a conceptual model of clean energy adoption based on trust and digitalization. The method used was a systematic literature review guided by PRISMA 2020 on articles obtained from Scopus, ScienceDirect, Taylor & Francis, and SINTA databases, where selected studies were analyzed thematically. The results of the study indicate that the adoption of renewable natural gas is influenced by green trust formed through credible digital information, institutional reputation, and customer experience. Perceived value encompasses economic, social, and symbolic benefits, as well as digital engagement that increases awareness and loyalty. Furthermore, barriers were identified in the form of perceived price risk, limited infrastructure, and low green energy literacy. This study concludes that green energy marketing needs to be directed at creating value based on trust and digital experiences, while also encouraging the strategic role of state-owned energy companies in building a trust ecosystem and cross-sector collaboration.